2018
DOI: 10.6023/cjoc201801047
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Aminothiophene Derivatives Catalyzed by Amano Lipase M from Mucor javanicus

Abstract: A series of 2-aminothiophene derivatives were synthesized by the Gewald reaction between α-active methylene nitrilthes and 2,5-dihydroxy-1,4-dithiane using amano lipase M from Mucor javanicus as biocatalyst. The method has the advantages of mild reaction conditions, biodegradability of catalyst and wide range of substrates compared with traditional catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Among the various types of enzymes, hydrolases undoubtedly play an important role because of their high stability, high selectivity, and nonnaturally catalytic activity . Recently, several enzymes have been used in multiple types of organic reactions, such as Gewald, aldol, retro‐Claisen reaction, Mannich, and Friedländer reactions . However, to the best of our knowledge, the synthesis of azaarene derivatives by enzymatic catalysis of the reaction between 2‐methylquinolines and aromatic aldehydes has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various types of enzymes, hydrolases undoubtedly play an important role because of their high stability, high selectivity, and nonnaturally catalytic activity . Recently, several enzymes have been used in multiple types of organic reactions, such as Gewald, aldol, retro‐Claisen reaction, Mannich, and Friedländer reactions . However, to the best of our knowledge, the synthesis of azaarene derivatives by enzymatic catalysis of the reaction between 2‐methylquinolines and aromatic aldehydes has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…14 Additionally, it is the advantages of these enzymes that are frequently reported in organic reactions catalyzed by enzymes. [15][16][17][18][19][20] Due to the aforementioned properties possessed by enzymes, researchers are currently focusing on the combination of enzymes and conventional catalysts to develop organic reactions that cannot be achieved by a single catalyst, such as photoenzymatic ones. [21][22][23] As a well-studied hydrolase, -chymotrypsin has been demonstrated that it can keep its activity in organic solvents.…”
mentioning
confidence: 99%